Trainspotting [videorecording (DVD)]. - Miller, Jonny Lee; Carlyle, Robert, 1961-; McGregor, Ewan, 1971-; Boyle, Danny (Lions Gate Home Entertainment, 2011)
Choose life. Choose a job. Choose a career. Choose a family. Choose Trainspotting. Director Danny Boyle thrills in this 'original, daring' tale of a group of young drug addicts wheeling through blue collar Edinburgh that earned an Academy Award for Best Adapted Screenplay. Trainspotting electrified audiences and critics with its hilariously dark humor, stunning visuals and sharp honest take on both the exhilarating highs, and the terrifying lows, of addiction.